Estimation accuracy of multi‐cell massive multiple‐input multiple‐output systems in correlated Rician fading channel. Issue 22 (7th October 2015) - AL‐Salihi, H.; Said, F.; Nallanathan, A.; Wong, K.
Abstract : The performance analysis of a multi‐user multi‐cell massive multiple‐input multiple‐output system that applies a conventional channel estimation technique, namely the linear minimum mean square error over correlated Rician fading is investigated. Based on the analysis, it is found that increasing the line‐of‐sight component can enhance the estimation accuracy.